Listeria Contamination in Milk-Processing Chain and Proficiency in Listeria monocytogenes Decontamination of Small-Scale Milk Retailers - Suppada Kananub; Papavarin Lertsakkongkul; Patsara Aryatawong; Wilailak Horhirunkhajohn; Nayika Pinniam; Praphaphan Krajanglikit; Kamonrat Sonthong; Suwicha Kasemsuwan (Journal of Food Quality)
Listeria spp. is an important foodborne bacterium. This microorganism can be discarded from milk using high temperatures such as pasteurization. The milk-processing methods of many small-scale retailers lack quality control. This study was to survey Listeria contamination at the farm and retailer levels. The retailers were to be interviewed for knowledge, attitude, and practice as well. Finally, we were to determine the heating processes employed to decontaminate microorganisms by the retailers using a reference strain of L. monocytogenes. Milk samples were collected from milk-collecting centers and small-scale retailers. In clinical trial, the processing measures were proved for the proficiency in L. monocytogenes decontamination. One out of 99 farms presented Listeria contamination, confirmed to L. marthii. Fifty small-scale retailers participated in the second part, including 13 males and 37 females. No Listeria spp. but Staphylococcus spp. and Bacillus spp. were identified in the processed milk. Data analyses revealed that the location of the retailer was significantly associated with the volume they routinely ordered per lot and the milk-processing time the retailers used to treat milk. Knowledge on raw milk contamination is significantly associated with the stocking or processing of the whole milk lot. Processing measures presale were significantly influenced by the gender of the retailer. The male retailer reportedly spent less time treating milk compared to their female counterparts. To assess the efficacy of the processing methods, a trial using L. monocytogenes as a reference strain was conducted. Interestingly, no L. monocytogenes was detected after sample treatment, but other microorganisms such as S. epidermidis, S. warneri, and Escherichia coli were found, suggesting potential issues with cross-contamination. In conclusion, while the trial implied that the retailers’ processes were effective in L. monocytogenes decontamination, the study highlighted inappropriate practices and the risk of cross-contamination. Continuous monitoring of product safety in small-scale milk retailers is imperative to ensure consumer well-being.